Cationic-Enhanced Spectrofluorimetric Method for Determination of Selective Serotonin Reuptake Inhibitor Duloxetine Hydrochloride in its Dosage Forms - A. Alarfaj, Nawal; A. Ammar, Reda; F. El-Tohamy, Maha (Asian Journal of Chemistry, 2013)
A highly sensitive, rapid, accurate and precise spectrofluorimetric method was developed for the determination of duloxetine hydrochloride in its pharmaceutical formulations. The proposed method is based on investigation of the fluorescence spectral behaviour of duloxetine hydrochloride in cetyl trimethylammonium bromide (CTAB) micellar system. In aqueous solution of borate buffer pH 9.9, the fluorescence intensity of duloxetine hydrochloride was greatly enhanced, 3-fold enhancement, in the presence of cetyl trimethylammonium bromide. The fluorescence intensity of duloxetine hydrochloride was measured at 382 nm after excitation at 275 nm. The fluorescence-concentration plot was rectilinear over the range of 1-70 ng/mL with lower detection limit of 0.5 ng/mL. The method was successfully applied to the analysis of duloxetine hydrochloride in its commercial dosage forms. The results were in good agreement with those obtained with the reported method. The application of the proposed method was extended to the stability studies of duloxetine hydrochloride after exposure to different forced degradation conditions, such as acidic, alkaline, oxidative and thermal conditions, according to ICH guidelines.